Electrostatic interaction due to patch potentials on smooth conducting surfaces - Fosco, Cesar Daniel (2013)
We evaluate the electrostatic interaction energy between two surfaces, one flat and the other slightly curved, in terms of the two-point autocorrelation functions for patch potentials on each one of them, and of a single function ψ which defines the curved surface. The resulting interaction energy, a functional of ψ, is evaluated up to the second order in a derivative expansion approach. We derive explicit formulae for the coefficients of that expansion as simple integrals involving the autocorrelation functions, and evaluate them for some relevant patch-potential profiles and geometries.